Straight Vessel Pattern and Rapid Filling Time: Characteristic Findings on Contrast‐Enhanced Sonography of Testicular Lymphoma. (22nd June 2016) - Lock, Guntram; Schmidt, Christa; Schröder, Claudia; Löning, Thomas; Dieckmann, Klaus-Peter
Abstract : Six patients with 7 lesions that were histologically confirmed as primary testicular lymphoma were preoperatively investigated with a standardized sonographic protocol including contrast‐enhanced sonography. Duplex and contrast‐enhanced sonography showed marked hypervascularization in all 7 lesions. On contrast‐enhanced sonography, the filling time of lymphomatous lesions was significantly shorter than the filling time of a size‐matched sample of 10 patients with seminomas ( P < .0001). The sonographic hallmarks of testicular lymphoma in our case series were as follows: (1) sharply demarcated homogeneous hypoechoic testicular lesions with marked hypervascularization; (2) a rapid (<7 seconds) filling time of contrast bubbles; and (3) a straight and parallel course of intralesional vessels on contrast‐enhanced sonography.